Transcript of Interview with a local leader in Lwengo district - Kinyera, Paddy Banya (Oil Movements: the Production and Government of Petro-(im)mobilities in East Africa, 2020)
Translated transcription
Keywords: Oil Infrastructure; East African Crude Oil Pipeline; Uganda